ANALISIS SEMIOTIKA DALAM LIRIK LAGU WIJAYAKUSUMA KARYA ARDHITO PRAMONO - Ratna Wulandari; Aswarini Sentana (Jurnal Sosial Humaniora dan Pendidikan, 2023)
This study aims to describe the semiotic analysis contained in the lyrics of a song entitled "Wijayakusuma" by Ardhito Pramono. This research method uses descriptive analysis. The results of this study reveal that, based on the results of a semiotic analysis of the lyrics of the song, the first trichotomy that often appears is the meaning of the index and also the symbol. The first trichotomy, namely Denotatum, has 12 data. There is 1 data which includes an icon, 4 indexes, and 7 symbols. Overall, the lyrics of the song semiotically mean love and longing for the beauty of nature so that its sustainability is maintained. After conducting research, it is hoped that this research will provide benefits in the development of semiotics. In addition, it is hoped that this research will provide benefits for writers who are interested in semiotics and know how to apply it.